Detection of glutamate dehydrogenase gene (gdh) in Streptococcus suis isolated from pigs - SONOWAL, S; BARUA, A G; HAZARIKA, R A; RAJKHOWA, S; BARUA, C C; BHATTACHARYA, D K (The Indian Journal of Animal Sciences, 2014)
The study was undertaken for the detection of glutamate dehydrogenase gene (gdh) in S. suis from pig isolates. The results showed that the PCR primers obtained for S. suis gdh gene amplified the DNA from all the 15 S. suis strains tested and no amplification product was obtained from the non- S.suis isolates. The PCR technique by targeting the gdh gene was found highly specific and sensitive and can be used successfully for the detection of S. suis isolates regardless of serotype or geographic origin as compared to the conventional biochemical and serological tests, which do not unambiguously differentiate S. suis from other related organisms.